Two-Stage Exams in Undergraduate Nursing Education: A Descriptive Study on the Reduction of Barriers and Grade Inflation - Rodall, Amy (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2026)
Purpose: Collaborative assessment, including two-stage exams, has been widely implemented in undergraduate education as both an assessment method and a learning strategy. In a two-stage exam, students complete an individual exam, then immediately complete the same exam in small groups. Although the benefits of two-stage exams are well supported in the literature, weighting practices can vary. This descriptive study examined systemic and individual barriers to assessment among undergraduate nursing students and explored the potential for grade inflation associated with two-stage exams.Method: A total of 130 first- and second-year students enrolled in a collaborative undergraduate nursing program in British Columbia were recruited for the study. A pre-exam survey captured descriptive data on perceived barriers and their impact on exam performance, while a post-exam survey assessed satisfaction with two-stage exams, perceived effects on knowledge retention, and reduction of barriers. Grade inflation, a cited concern in the literature, was quantified by analyzing stage-one and stage-two exam scores across six undergraduate nursing courses using theoretical weighting scenarios.Results: Some participants (69%) identified with at least one barrier to assessment, with the most common being test anxiety (59.2%); anxiety, stress, or mental health concerns (46.1%); and attention-deficit/hyperactivity disorder, attention deficit disorder, or Autism spectrum disorder (26.9%). Most participants (86.1%) indicated that two-stage exams helped to reduce barriers to assessment, primarily by allowing them to revisit the question (67.6%), providing them with a second chance (65.7%), and improving their understanding of the question (64.8%). Additionally, 90% (n = 97) stated that they felt better prepared to apply this knowledge in future courses or clinical settings. Perceptions of increased knowledge mastery was rated as 4.47 on a five-point scale, participant satisfaction was 4.4, and participation was 4.65. Grade inflation ranged from 0.33% for an A+ grade weighted at 90/10 to 9.63% for a D grade weighted at 75/25.Conclusion: Findings highlight the prevalence of assessment-related barriers among nursing students and suggest that two-stage exams may help mitigate these challenges. Quantifying grade inflation across weighting scenarios provides faculty with evidence to guide decisions regarding the implementation of two-stage exams.